A Circuit-Based Football Heading Exercise Model in Football School Ages 14-17 Years - Setiawan, Romli Riski (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
This research aims to produce heading soccer based training models to improve the accuracy of headings in soccer games. The research method used in this study is the research and development method (Research and Development) of Borg and Gall by using 10 stages and with the research subjects are soccer athletes aged 14-17 years in football schools in Jambi Province. This research begins with needs analysis, planning, product making, testing, revision and final products. The effectiveness test of the model using the Main Field Test is used to determine the level of athlete?s heading ability before and after the treatment of the training model based on circuit-based soccer skills developed. The results of the study show that the product model of this exercise is feasible to use, in the results of small group trials and large groups can explain that the model as a whole can be done well. In the results of the effectiveness test showing an increase in heading training results from the initial tests and final tests after being given a training model treatment, these results indicate that the resulting circuit based soccer heading training models can be used and can effectively improve the heading ability of athletes aged 14-17 years. Based on the results of the output using SPSS 16 that the average value of soccer heading before being given a training model is 18.04 and after being given treatment with a training model 23.78 means that the average value of soccer headings is increased. Kata Kunci: Model latihan, heading sepakbola, sirkuit,